Stressing Out About the Heart: A Narrative Review of the Role of Psychological Stress in Acute Cardiovascular Events - Musey, Paul (Acad Emerg Med, 2019)
OBJECTIVES: Survivors of acute cardiovascular disease events, such as acute coronary syndrome and stroke may experience significant psychological distress during and following the acute event. Long term adverse effects may follow, including the development of posttraumatic stress disorder (PTSD) and increased overall all-cause mortality and recurrent cardiac events. The goal of this concepts paper is to describe and summarize the rates of adverse psychological outcomes, such as PTSD, following cardiovascular emergencies, to review how these psychological factors are associated with increased risk of future events and long-term health, and to provide a theoretical framework for future work. METHODS: A panel of 2 board certified emergency physicians, 1 with a doctorate in experimental psychology, along with 1 PhD clinical psychologist with expertise in psychoneuroendrinology were co-authors involved in the paper. Each author used various search strategies (e.g. PubMed, Psycinfo, Cochrane, and Google Scholar) for primary research, and review articles related to their section. The references were reviewed and evaluated for relevancy and included based on review by the lead authors RESULTS: A meta-analysis of 24 studies (N >2300) found the prevalence of ACS-induced posttraumatic stress disorder (PTSD) at nearly 12%, while a meta-analysis of 9 studies (N=1138) found 25% of survivors of transient ischemic attack (TIA) and stroke report PTSD symptoms. Presences of PTSD doubles 3-year risk of CVD/mortality risk in ACS survivors. Cardiac patients treated during periods of ED overcrowding, hallways care, and perceived poor clinician-patient communication appear at greater risk for subsequent PTSD. CONCLUSION: Psychological stress is often present in patients undergoing evaluation for acute CVD events. Understanding such associations provides a foundation to appreciate potential contribution of psychological variables on near and long-term cardiovascular recovery, while also stimulating future areas of research and discovery.